2015
DOI: 10.1152/jn.00796.2014
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic injury suppresses hypoxia-induced electrographic seizures and the background EEG in a rat model of perinatal hypoxic-ischemic encephalopathy

Abstract: Zayachkivsky A, Lehmkuhle MJ, Ekstrand JJ, Dudek FE. Ischemic injury suppresses hypoxia-induced electrographic seizures and the background EEG in a rat model of perinatal hypoxic-ischemic encephalopathy. J Neurophysiol 114: 2753-2763, 2015. First published September 9, 2015 doi:10.1152/jn.00796.2014.-The relationship among neonatal seizures, abnormalities of the electroencephalogram (EEG), brain injury, and long-term neurological outcome (e.g., epilepsy) remains controversial. The effects of hypoxia alone (Ha)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
7
14
0
Order By: Relevance
“…A). This phenomenon has been previously reported in a similar animal model of continuous seizures over a 2h recording period (Zayachkivsky et al, ). Human EEGs also show a reduction in overall seizure power with treatment (Pan et al, ).…”
Section: Resultssupporting
confidence: 84%
“…A). This phenomenon has been previously reported in a similar animal model of continuous seizures over a 2h recording period (Zayachkivsky et al, ). Human EEGs also show a reduction in overall seizure power with treatment (Pan et al, ).…”
Section: Resultssupporting
confidence: 84%
“…We observed that this rodent model of neonatal HI results in a characteristic pattern of behaviors consisting of both focal and multifocal seizures. Previous studies have also observed both focal and multifocal seizure semiology, 7,37,38 such as circling toward the ischemic side during neonatal rodent HI. [10][11][12] In conjunction, we observed clear asymmetries in the power spectrogram and cfos mapping of neuronal activity.…”
Section: Discussionmentioning
confidence: 90%
“…Vannucci et al, 1995Vannucci et al, , 1997Vannucci et al, , 2001) simply mimic the effects of the endogenous hypercapnia, which are always associated with BA. In contrast to this, in current rodent models of BA and/or HIE which are based on exposure of rat and mouse pups to pure hypoxia induced by a gas mixture with a low O 2 (typically 4-8 % O 2 in N 2 ) (Greggio et al, 2009;Jensen et al, 1991;Rakhade et al, 2011;Rodriguez-Alvarez et al, 2015;Zanelli et al, 2014;Zayachkivsky et al, 2015), seizures are triggered already during the insult. Moreover, pure hypoxia (which does not occur under reallife physiological or pathophysiological conditions) evokes an immediate brain-confined alkalosis (Pospelov et al, 2020), which is exactly the opposite of what happens during asphyxia.…”
Section: Discussionmentioning
confidence: 99%